EFEKTIVITAS BIMBINGAN KELOMPOK MENERAPKAN ASSERTIVE TRAINING PADA PENINGKATAN INTERAKSI SOSIAL - Mawarni, Dini; Yuline, Yuline; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The research was conducted with the effectiveness of group guidance by implementing assertive training in increse the social interaction students at SMP Negeri 2 Pontianak. With the experimental method, the true experimental design uses a posttest only control design. The research samples was selected using a probability sampling technique with simple random sampling. The sample consisted of 20 students who were separated into two groups, namely an experimental group containing 10 people and a control group containing 10 people. Data analysis was carried out using the independent sample t-test. The results show that there are differences in the average values obtained from the two groups. The average score for the experimental group that was given tratment in the form of group guidance by applying assertive training was 133,5. Meanwhile, the average score for the control group that was given tratment in the form of group guidance using conventional methods was 107,6. Next, the Sig value is obtained. (2-tailed) of 0,000 < 0,05, indicating a significant difference between the two groups, so Ha is accepted. So it is concluded that group guidance by implementing assertive training is very effective in increasing the social interaction of students at SMP Negeri 2 Pontianak.